Synthesis of surface water hydrology ... - Neil, C. R. (University of Alberta Library, 1979)
The drainage system of the study area consists of a number of rivers draining from the west and from the east into the Athabasca River north of Fort McMurray, as well as a few rivers which join the Athabasca near Fort McMurray and drain areas to the south and east. Runoff from within the study area itself contributes less than 10% of the average flow in the Athabasca River at the northern boundary of the study area. Roughly 60% of annual runoff occurs in the 4-month period April through July. Runoff represents on the average only about 20% of the precipitation that falls on the area, the remainder being returned to the atmosphere by evaporation and transpiration. Although snowfall constitutes only about 30% of precipitation, its proportional contribution to runoff is generally much greater. On the east slopes of the Birch Mountains, runoff from rainfall appears to be remarkably small. Although the spatial variability of average runoff over the study area is not well defined by available streamflow data, it ...